Risk Society and Amoral Morality - Nedeljković, Radica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The modern world is the world of change. Modernity changed all aspects of life in width and depth. The changes are so fast and so many people have impression that they are trapped in a multitude of events that they cannot understand nor control. Instead of society as a system, we are talking about society as a network of different relationships of individuals and social groups. Instead of a harmonious society as a space in which the man resides, developing their potential and needs, we are talking about society as a threatening force that destroys everything in its way as "Moloch" (Giddens), the "risk society" (Beck) in which the doctrine produced in equal measure the conditions for prosperity, but also the risks and destruction; the simulation of society " (Baudrillard) which glorifies lies and deceit. Instead of society as a community, we are talking about the disappearance of society (Popper). Can we, therefore, rationally understand and express the world, the world of modernity; this world of profound change resembles the maze in which we are lost and wandering without meaning? Starting with Ulrich Beck and his theory of the risk society, the author points out that the way in which the western civilization started, which is imposed as a mandatory form for the rest of the world, leads to amoral morality. The ideology of progress, which is irrational and without a clear vision and clearly defined values,​​ pushes us into an uncertain future of numerous risks and ever growing individualism. Thus, we come to the conviction that without common values, collective values, we are lost in this world of risk. Solidarity and trust are the key values ​​for the stable community, but they are non-existent in the risk society dominated by individualism. In the period of uncertainty in the risk society, only religion provides a healthy basis for communal living. Therefore, the way out of the crisis is not in politics, which is placed at the service of the economy, but in ethics and religion. However, the key issue is how to develop these values without common models of values, which brings us to the question of religion. Egoistic blind hedonism pushes people into moral scarcity and lack of a sense of the common good, mercy, solidarity, and the supreme value. Each instance of individualism inevitably leads to suffering. Everything boils down to interest, and losing sense of the supreme good, mercy, and solidarity. This foolish epoch we live in, where Thanatos forces grows stronger, can only be remedied by returning to our Orthodox roots and turning towards "equal" (Njegoš) civilization, Orthodox Russia.
Keywords: modernity; change; amoral morality; risky society